Golf - Ditchfield, Christin (Danbury, Conn Children's Press, 2003)
Examines the history, basic rules, terminology, and major events of the sport of golf
Tigermania -- Years ago -- The equipment -- The rules -- On the course -- The professional tour
Includes bibliographical references (p. 44) and index
Hurg
5 18
Keywords: Golf